La Racionalidad Ecológica de los Costos Históricos y el Conservadurismo (2021)
The principles characterizing the traditional revenue-expense approach  to accounting cannot be traced back to a particular historical event; they are ecologically rational. Their functionality is the result of cultural evolution, not of a specific human design. This is why efforts to defend the assets and liability approach, endorsed by standard-setters have encountered serious difficulties. Only the latter approach is clearly based on a specific economic model: neoclassical economics. In contrast, it is argued that a solid basis for explaining the rationale of the culturally evolved accounting principles can be found in behavioral economics. These principles are in line with human behavior as found in numerous laboratory and field experiments. Especially with respect to prospect theory, a close parallel is identified. Furthermore, this analysis is combined with a view of the market process in the economy. Financial accounting according to the asset-liability approach does not add new information to the market process, it only summarizes at company level the information provided by the market. In contrast, the revenue-expense approach provides private information to the market as described by Hayek (1945). The revenue- expense approach thus results compatible with the organization of the market economy.